2015
DOI: 10.1039/c4tc02210f
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization-enhanced magnetism in SnO2nanoparticles and its correlation to photoluminescence properties

Abstract: A high value of magnetic moment of 0.08 emu g−1at room temperature for SnO2nanoparticles (NPs) was observed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…And, on the other hand, the broad orange band is replaced by a narrow emission line at nm. Previous photoluminescence (PL) studies in SnO2 nanoribbons obtained by laser ablation reporteda strong broad luminescence peak around 620 nm [23][24][25] associated with oxygen vacancytin interstitials leading to formation of trapped states in the bandgap 25 . Here, we observe that orange emission narrows, what suggests local changes in the electronic levels probably as a consequence of changes of the local crystal microstructure of the SnO2 particles attached to the Ga2O3 nanowire.…”
Section: Methodsmentioning
confidence: 99%
“…And, on the other hand, the broad orange band is replaced by a narrow emission line at nm. Previous photoluminescence (PL) studies in SnO2 nanoribbons obtained by laser ablation reporteda strong broad luminescence peak around 620 nm [23][24][25] associated with oxygen vacancytin interstitials leading to formation of trapped states in the bandgap 25 . Here, we observe that orange emission narrows, what suggests local changes in the electronic levels probably as a consequence of changes of the local crystal microstructure of the SnO2 particles attached to the Ga2O3 nanowire.…”
Section: Methodsmentioning
confidence: 99%
“…This development rooted back in 1998 when Ohno et al [1] reported the existence of ferromagnetism in Mndoped GaAs at a temperature greater than 100 K. Earlier metal oxides like TiO 2 [2], ZnO [2], SnO 2 [3], and In 2 O 3 [2] were doped with transition metals (TM) such as Co [4,5], Mn [6], Fe [7], Cu [8,9], Ti [10], and V [10] and also surface functionalized with organic molecules [11] to create high-moment DMS materials. Among metal oxides, ZnO is widely used in optoelectronic and spintronic applications [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the varieties of ETL materials, n-type low WF metal oxides, including ZnO, SnO 2 , and TiO 2 , etc., have been popularly used in OSCs and other organic electronics, such as perovskite solar cells and organic light-emitting diodes. [20][21][22][23][24][25][26] Although significant progress has been achieved based on metal oxide ETLs, the intrinsic drawbacks of such materials lead to unsatisfactory performances and stability, which need further improvements. Specifically, due to the ''Fermi level pinning effect,'' severe charge barriers exist at the interface between the metal oxide ETLs and organic semiconductors, resulting in inefficient charge transfer and accumulation.…”
Section: Introductionmentioning
confidence: 99%